2016
DOI: 10.1002/bit.25962
|View full text |Cite
|
Sign up to set email alerts
|

Chemical inhibition of autophagy: Examining its potential to increase the specific productivity of recombinant CHO cell lines

Abstract: Chinese hamster ovary (CHO) cells activate and undergo apoptosis and autophagy for various environmental stresses. Unlike apoptosis, studies on increasing the production of therapeutic proteins in CHO cells by targeting the autophagy pathway are limited. In order to identify the effects of chemical autophagy inhibitors on the specific productivity (qp ), nine chemical inhibitors that had been reported to target three different phases of autophagy (metformin, dorsomorphin, resveratrol, and SP600125 against init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 36 publications
2
18
0
Order By: Relevance
“…Apoptosis and Autophagy are programmed cell death processes, which can be triggered by nutrient depletion or environmental stress, potentially decreasing overall cell health and cell culture performance. Supplementation with apoptosis inhibitors and autophagy inhibitors has been evaluated, in some cases improving recombinant protein expression. Most of these supplements are not widely used due to the cost at manufacturing scale.…”
Section: Recent Advances In Medium Developmentmentioning
confidence: 99%
“…Apoptosis and Autophagy are programmed cell death processes, which can be triggered by nutrient depletion or environmental stress, potentially decreasing overall cell health and cell culture performance. Supplementation with apoptosis inhibitors and autophagy inhibitors has been evaluated, in some cases improving recombinant protein expression. Most of these supplements are not widely used due to the cost at manufacturing scale.…”
Section: Recent Advances In Medium Developmentmentioning
confidence: 99%
“…A particularly successful example was the transfection of two inducible anti‐apoptotic genes into Chinese Hamster Ovary (CHO) cells that enabled increased fed‐batch viable cell concentrations as well as recombinant protein production (Figueroa et al, ). More recently, factors that modulate autophagy have also been used to increase CHO cell protein production up to ∼3‐fold in fed‐batch, in particular using 3‐methyladenine (a putative inhibitor that can also induce autophagy with prolonged exposure) (Baek, Kim, Kim, Lee, & Lee, ; Jardon et al, ; Nasseri et al, ). Combined strategies to inhibit apoptosis and induce autophagy have also been developed (Lee, Ha, Park, & Lee, ).…”
Section: Introductionmentioning
confidence: 99%
“…Two of the pathways that were found to be highly enriched in the exponential and stationary phases were the mTOR and autophagy pathways. The mTOR pathway has been manipulated previously in CHO cells to improve production efficiencies, and recently autophagy in CHO cells have gained attention as an opportunity for controlled cell death in bioprocess . In our study, we identified 18 phosphoproteins from the mTOR pathway, including the components of both mTORC1 and mTORC2 complexes.…”
Section: Resultsmentioning
confidence: 98%
“…Pathway analysis of phosphoproteomic data also revealed a significant enrichment of autophagy‐related proteins with differential expression between Day 2 and Day 4 of the batch suspension culture. Recently autophagy has gained importance in bioprocess as an opportunity to genetically and chemically control cell survival and productivity . It is therefore important to have a detailed understanding of the autophagic pathway in order to select relevant genes and chemical targets to manipulate autophagy in CHO cells to enhance the production of biotherapeutics .…”
Section: Discussionmentioning
confidence: 99%